2020
DOI: 10.1136/bcr-2019-232498
|View full text |Cite
|
Sign up to set email alerts
|

Management of afferent loop syndrome after Roux-en-Y subtotal gastrectomy and choledocolithiasis with recurrent cholangitis

Abstract: Afferent loop syndrome is a rare complication after gastrectomy with Billroth II or Roux-en-Y reconstruction, caused by an obstruction in the proximal loop. The biliary stasis and bacterial overgrowth secondary to this obstruction can lead to repeated episodes of acute cholangitis. We present the case of a male patient who had previously undergone gastrectomy with Roux-en-Y reconstruction and later experienced multiple episodes of acute cholangitis secondary to choledocolithiasis. He underwent an open explorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In chronic afferent loop syndrome, the patient will have prolonged partial small intestine obstruction features. In chronic afferent loop syndrome on long run, the obstruction will cause pancreatitis, cholangitis and overgrowth of microbes in afferent limb of the jejunum leading to sepsis (2)(3)(4)(5). Although patients with chronic afferent loop syndrome will have cholangitis, it is better to rule put other causes like stricture on hepaticojejunal anastomotic site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In chronic afferent loop syndrome, the patient will have prolonged partial small intestine obstruction features. In chronic afferent loop syndrome on long run, the obstruction will cause pancreatitis, cholangitis and overgrowth of microbes in afferent limb of the jejunum leading to sepsis (2)(3)(4)(5). Although patients with chronic afferent loop syndrome will have cholangitis, it is better to rule put other causes like stricture on hepaticojejunal anastomotic site.…”
Section: Discussionmentioning
confidence: 99%
“…It can be acute or chronic based on its duration of occurrence after the Bill Roth II reconstruction. Acute one will present with in early post-operative complete obstruction but chronic afferent loop syndrome can present with partially obstructed small bowel features for weeks, months and even years (2). The causative agents are classi ed as intraluminal, intramural and extrinsic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two retrospective cohort studies showed that the incidence of ALS in gastric cancer patients undergoing Billroth II and Roux-en-Y reconstruction was 1.01% and 0.2% respectively, and all were caused by adhesion, internal herniation, and peritoneal recurrence[ 1 , 2 ]. As for treatment, traditionally, surgery is the cornerstone of treatment for ALS, which includes converting a Billroth II to a Roux-en-Y[ 8 ], creating a Braun anastomosis between the afferent and efferent loops in a Billroth II[ 9 ], or excising redundant loops and reconstruction[ 10 ]. However, surgery is not suitable for every patient with ALS[ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%